Paths to post-nationalism a critical ethnography of language and identity - Heller, Monica (New York ; Oxford : Oxford University Press, 2011)
Monica Heller shows how hegemonic discourses of language identity and the nation-State are destabilized under new political and economic conditions.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: French language -- Political aspects -- Canada; French language -- Social aspects -- Canada; French-Canadians -- Language; Nationalism; Globalization